Development of monoclonal antibodies to IFITM1 protein using scFv-phage display libraries - Di Pietro, Francesco (The University of Edinburgh, 2021)
BACKGROUND AND AIMS: Immunotherapy using monoclonal antibodies has been proven to be highly effective in the treatment of a variety of cancers and studies are still focusing on the development of new antibodies and new therapeutic combinations involving them. The role that the IFITM1 protein plays in cancers remains unclear, however, the protein has been associated with poor prognosis and progression of many types of cancers and its attenuation leads to the inhibition of growth, invasion and migration of the tumour cells. The IFITM1 protein is a transmembrane receptor whose conformations on the plasma membrane is known to be regulated by interferon signalling. The project examines the use of oligomeric isoforms of IFITM1 protein to isolate novel scFv antibodies from antibody phage libraries. The aim is to identify epitopes specific for the monomer and oligomers of interest that can be used to better understand the role of IFITM1 in cancer and also generate a potential therapeutic agent based on agonist or antagonist actions. Hypothesis: can monoclonal antibodies be designed for all three of the IFITM1 oligo-forms to study conformational changes in human cancer cells? METHODS: Monomeric and oligomeric IFITM1 proteins, purified from a bacterial paste were tested for denaturing resistance in order to confirm preliminary data and annotate the conformationally variants produced bacteria. A naïve phage antibody display library was used in a biopanning process against the purified fractions of the IFITM1 protein. The specificity of the selected clones was assessed by phage ELISA. RESULTS: Western blot results confirm preliminary data defining the purified monomers and oligomers as stable forms of IFITM1 protein. The biopanning rounds showed positive enrichment of the specific epitopes. ELISA assays confirmed binding specificity of the selected clones in both IFITM1 and its purified oligomeric species with some of the isolated scFvs exhibiting high specificity and reactivity. The overall aim of the thesis to develop isoform specific antibodies to the IFITM1 protein was achieved. This will allow further validation of recombinant biologics to the IFITM1 pathway to shed light on IFITM1 functions both in viral and cancer settings.
The development of monoclonal antibodies to IFITM1 protein using scFv-phage display libraries
Keywords: IFITM1 Protein; Monoclonal Antibodies; Monoclonal Antibodies to IFITM1 Protein; scFv-phage Display Libraries; Immunotherapy; transmembrane receptor; plasma membrane; scFv antibodies; human cancer cells